Assessment of the potential of biomass chemical looping combustion with CO2 capture from experimental results at the 20 kWth scale with olive stone - Alberto Abad; María T. Izquierdo; Teresa Mendiara; Luis F. de Diego; Raúl Pérez-Vega; Francisco García-Labiano (Applications in Energy and Combustion Science, 2025)
The bioenergy with CO2 Capture and Storage (BECCS) concept has the potential for the carbon dioxide removal (CDR) from the atmosphere. Among the negative emissions technologies (NETs), Chemical Looping Combustion (CLC) has low economic and energetic costs due to the inherent CO2 capture by splitting the combustion in fuel and air reactors. The fuel combustion happens in the fuel reactor, where CO2 is concentrated and separated from air. In this work, the combustion of olive stone is performed in a CLC unit at the 20 kWth scale using a highly reactive iron ore. The tests analyse the effect on the combustion efficiency and the CO2 capture of the main operating conditions: reacting temperature (800-970 °C), oxygen carrier-to-fuel ratio (ϕ=1-3) and specific solids inventory (140-720 kg/MWth). Tests at a lower scale (6 kWth) evaluate the effect of some design parameters. A total of 60 h of olive stone combustion were performed. No relevant differences on the CO2 capture were observed among these scales. Full combustion was not achieved due to the high volatile content of the biomass and the uncompleted oxidation of char gasification products, but the combustion degree was improved at the highest scale due to the proper development of the characteristic fluid dynamic of a circulating fluidized bed. A cross-effect was observed between CO2 capture and combustion efficiency: the later decreased as the first increased due to the higher char conversion. CO2 capture values above 90 % may be feasible with oxygen demand values around 15 % operating at fuel reactor temperatures above 950 °C and specific solids inventory values about 300-400 kg/MWth.